2017
DOI: 10.1002/cb.1661
|View full text |Cite
|
Sign up to set email alerts
|

Experiential tourist shopping value: Adding causality to value dimensions and testing their subjectivity

Abstract: Previous literature on consumer behavior has tackled the experiential approach in retailing services in depth; however, most of the previous studies have concentrated on the simultaneous but not concatenated effects of value dimensions on satisfaction and/or loyalty. Furthermore, tourists' shopping behavior remains an underdeveloped area of study from the experiential perspective. This work explores experiential tourist shopping value, aiming to (a) explain tourists' loyalty to retailers by adding causality to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 94 publications
(233 reference statements)
0
18
0
2
Order By: Relevance
“…It is well‐established in the marketing literature that a satisfied customer will be more likely to return (e.g., Correia Loureiro & Kastenholz, ). For example, in the value creation chain of relationships, it has been shown that enjoyment derived from shopping is directly related to loyalty (Gallarza et al, ). Because customer satisfaction and customer well‐being proposed in the current study are both attributable to the consumption experience, it follows that both types of satisfaction should increase revisit intention.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well‐established in the marketing literature that a satisfied customer will be more likely to return (e.g., Correia Loureiro & Kastenholz, ). For example, in the value creation chain of relationships, it has been shown that enjoyment derived from shopping is directly related to loyalty (Gallarza et al, ). Because customer satisfaction and customer well‐being proposed in the current study are both attributable to the consumption experience, it follows that both types of satisfaction should increase revisit intention.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Moreover, the extant value creation literature has often examined how an external context would induce varying consumer value such as emotional and cognitive values and, in turn, would impact consumer outcomes such as satisfaction and loyalty (e.g., Bendapudi & Leone, ; Gallarza, Fayos Gardó, & Calderón, ; Mathwick, Malhotra, & Rigdon, ; Sweeney & Soutar, ). This line of research seems to suggest that value derived from an external context (e.g., shopping mall and restaurant) would invariably enhance consumer outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Par ailleurs, à l’instar des recherches de Johnson et al (2006) sur la fidélité, la capacité de la valeur à prédire la satisfaction pourrait être comparée, au fur et à mesure du cumul d’expériences, avec d’autres variables contribuant à la formation de la satisfaction (par exemple, la qualité perçue). Dans le prolongement des travaux de Gallarza et al (2016b, 2017b), les résultats obtenus pourraient aussi être approfondis par une meilleure considération de la nature multidimensionnelle de la satisfaction (cognitive et affective) et des effets séquentiels des dimensions de la valeur sur la satisfaction (via l’étude des relations causales potentielles entre les sources de valeur). Au-delà de l’étude des effets de modération, il semble essentiel, à l’instar des réflexions sur le lien satisfaction-fidélité et valeur-fidélité (Kumar et al, 2013 ; Lichtlé et Plichon, 2008), d’enrichir la compréhension du lien valeur–satisfaction par une meilleure prise en compte des phénomènes potentiels de non-linéarité ou d’asymétrie.…”
Section: Resultsunclassified
“…Following the example of the research by Johnson et al (2006) on loyalty, the capacity of value to predict satisfaction could also be compared, as experience is accumulated, with other variables contributing to the creation of satisfaction (for example, perceived quality). In continuation of the work of Gallarza et al (2016bGallarza et al ( , 2017b, the results could be further developed by better consideration of the multidimensional nature of satisfaction (cognitive and affective) and the sequential effects of the dimensions of value on satisfaction (through the study of potential causal relationships between the sources of value). In addition, studying the effects of moderation, it seems essential, pursuant to thinking about the satisfaction-loyalty and value-loyalty links (Kumar et al, 2013;Lichtlé and Plichon, 2008), to enrich understanding of the value-satisfaction link by taking greater account of the potential phenomena of non-linearity or asymmetry.…”
Section: Limitations and Future Researchmentioning
confidence: 99%